Status and Tasks of Ordering Payment of Compensation for Loss of Life - M. A. Bychkova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2014)
The problem of determining the size and legal basis of compensation due to the loss of life has never been the subject of systematic analysis. At the same time, the solution to this problem is not only economic but also social and moral- ethical significance. First there is collected and analyzed data on an array of payments in connection with all the important occasions for their payments for the past 15 years. Formulate proposals to address this systemic problem.